Aprendizagem e competências empreendedoras: estudo com artesãs no Estado do Ceará - Moura, Danielle Aparecida Amaral de (2023)
Studies on the life experiences of women entrepreneurs are important gaps to be filled for the advancement of this research area. Understanding the recurring competences of these women and comprehending their life experiences enable improvements in their performance in entrepreneurial ventures (VASCONCELOS, 2014). Female artisans are embedded in an important local economic context with an impact on job creation and income generation, where entrepreneurs need to learn and develop competences. The theoretical foundations of this study are the entrepreneurial learning models proposed by Politis and Gabrielsson (2005) and the entrepreneurial competence model by Man and Lau (2000). In this context, the main objective of this research is to investigate the contribution of entrepreneurial learning to the development of entrepreneurial competences among artisans in the State of Ceará. Thus, this research has the following specific objectives: to analyze the acquired entrepreneurial knowledge, to examine the experiences of entrepreneurial career, to investigate the process of entrepreneurial learning transformation and the factors influencing the transformation process from experience to knowledge, and to explore the entrepreneurial competences of artisans in the State of Ceará. Regarding the methodology, this research adopts a qualitative and descriptive nature, conducted through semi-structured interviews with eight artisans and three independent leaders working in education, management, and consulting with extensive experience in the crochet craft sector in the State of Ceará. The data were analyzed using content analysis and operationalized with the ATLAS.ti 7 software. The results indicate that artisans possess skills in recognizing opportunities and are seeking further knowledge to manage the obligations related to their new business. It was identified that artisans learn through experiential processes, that is, through daily experiences, teamwork, studies, courses, among others. Artisans do not have experience in establishing businesses; however, they have experience in administration and in the specific sector of their business. It was found that the predominant mode of transformation process from experience to entrepreneurial knowledge among artisans is exploitation. Success, causal logic, and specialist career orientation are the factors that exert the greatest influence on this process, aligning with the exploitative mode. The six entrepreneurial competences from the model proposed by Man and Lau (2000) influence the performance of artisans: administrative, conceptual, opportunity-seeking, relationship-building, strategic, and commitment. The entrepreneurial competences of commitment and strategic thinking are the most well-characterized. Lastly, a strong connection between the process of entrepreneurial learning and the development of entrepreneurial competences among artisans was identified.